The Great Lakes water wars - Annin, Peter (Island Press, 2018)
For over a century the Great Lakes have been the target of controversial diversion schemes to sell, send, or ship water to thirsty communities, sometimes far from the source. In 2008, eight US states signed the historic Great Lakes Compact designed to protect the region's precious freshwater resources. Now water diversion controversies of a different kind are pitting communities and states against one another. Will the water wars ever be settled? With three new chapters and significant revisions that bring the story up to date over the past decade, this is the definitive behind-the-scenes account of the people and stories behind hard-fought battles to protect this precious resource that makes the region so special for the millions who call it home.